Analysis of Differences in Stock Price and Stock Volume of Trade Before and After Annual Report Award (ARA) Announcement in 2009-2016 in Award Winning Companies Listing In Indonesia Stock Exchange - Nur Widyawati; Ratna Ariesta (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2020)
This study aims to examine whether there are differences in stock prices and trading volume before and after the announcement of the Annual Report Award (ARA) at Award-winning companies. The sample of this research was obtained using purposive sampling method. Based on the existing criteria, 32 companies were obtained as the research sample. Hypothesis testing is done by using paired sample t-tests which were previously tested for normality first on each variable. The results of the study showed that there were no significant differences in share prices and trading volume before and after the announcement of the Annual Report Award (ARA) 2009-2016. Able to change investor decisions in investing